The impact of Economic Freedom and Democracy on Income Inequality: Empirical Evidence from Sub-Saharan African Countries - Nazirou, Sabi Couscous Mouhamadou (Archives of Business Research, 2022)
Throughout our study entitled the impact of economic freedom and democracy on Income Inequality: empirical evidence from Sub-Saharan African countries. We have demonstrated that the economic freedom which is defined as the elementary right of all humans to have control on his or her own labor and property and an important impact on the economic growth. Individuals have the freedom to work, to produce, to consume and to save or invest the way they want in an economically free society. We use the measure of Fraser Institute's economic freedom from the world summary index (EF). A composite of five major sub-indices: Access to sound money index (SM), Freedom to trade internationally index (FT), Government size index (GV), legal structure and security of property rights index (PR), and regulation of credit, labor and business index (RG). The results show that the Freedom to trade internationally index (FT), the Government size index (GV), the regulation of credit, labor and business index (RG) have negative impact on the income inequality. Concerning the Governance, Government Effectiveness, Rule of Law, and Regulatory Quality is negatively related to Income Inequality. Nevertheless, the Control of Corruption and the coefficient of Political Stability and Absence of Violence have a positive impact on Income Inequality. The stability promotes the income inequality and through the protest and demonstration by the least privileged leads the government to reconsider the system of ruling. Our control variables such as economic growth and population throughout the four estimations they show none significance with the Income Inequality. So basically the economic growth doesn’t affect the income inequality in Sub-Saharan Africa. As Africa financial institutions, the Banks have a clear mandate to support the Regional Communities, to strengthen strategies and to lower the income inequalities across countries and within countries. The inclusive growth plans and agenda of the Banks and their new Long Term Strategy will position the Bank as a leading institution to promote activities that foster economic growth in an inclusive